10-th Spring School on Acoustics and Applications - LINDE, Bogumił B.J. (Archives of Acoustics, 2007)
Sopot, Poland, May 12-15, 2007 Following nearly 30-year tradition of Springs Schools, it is our great pleasure to invite you to participate in the 10-th School on Acousto-Optics and Applications, which will be held in Sopot, Poland, from 12-th of May till 15-th of May, 2008. The 10-th School on Acousto-Optics and Applications focuses on all physical aspects of light and sound interaction. The School provides an insight into recent developments of both pure and applied acousto-optics. In particular, the scientific topics of the School include: theoretical and experimental studies of light diffraction by ultrasonic waves, acousto-optic devices and their applications in light modulation and deflection, signal processing, ultrasonic imaging and tomography, acousto-optic materials, photoacoustic spectroscopy, photothermics.